ANALISIS PENGARUH FAKTOR KELENGKAPAN PRODUK, KUALITAS PRODUK DAN CITRA PRODUK TERHADAP LOYALITAS KONSUMEN BASMALAH MARKET KARANGGENENG - Nurus Safa’atillah (JURNAL PROFIT, 2019)
The purpose of this study was to determine the complecateness of the product, product quality, and product image effect partially or simultaneously on consumer loyality to the market Basmallah Karanggeneng Lamongan, as well as to determine the complecateness of the product, product quality, and product image, which is more dominant effect on consumer loyality partners market Basmallah Karanggeneng Lamongan. From the results obtained t test the completeness of the product (3.244), product quality (6.615),and the image of the product (11.217). The independent variable range of product, product quality and product image has t hitung> t table (1.984) then H0 rejected and Ha is received so at it can be interpreted that the independent variable range of products, product quality and product image partially has a significant effect on the dependent variable customer loyality. And the rest results obtained F hitung (94.545), while F table (2,70) for F count> F table then H0 rejected and Ha is received so that it can be interpreted that the independent variable range of products, product quality and product image simultaneously have a significant effect on the dependent variable consumer loyality.